Polycyclic Ovarian Syndrome and it Effect on Fertility - Enid, Athari Hussein; Diaf, Zahraa Hassan; Mawla, Mohammed Ozara; Radad, Ghofran Saud; Dawud, Zahraa Fouad; Jumaa, Saja Abdullah (American Journal of Biomedicine and Pharmacy, 2024)
Polycystic ovary syndrome is the most common endocrinological disorder in women of reproductive age. It is commonly associated with anovulatory subfertility, for which there are a range of treatment options available to help them conceive. These options are given in a step-wise manner with an appropriate selection of patients to maximise success rates with minimal complications. This review discusses the importance and involvement of multidisciplinary care when offering treatment to women with subfertility. Multidisciplinary care gives an excellent opportunity to identify, assess risk, and potentially prevent future morbidities and complications while treating women for fertility issues. We have also summarised the various options available for fertility treatment: pharmacological treatments, nonpharmacological intervention, and assisted reproductive technology.